If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-1) + -3 = -2 + -1x Multiply 5 * -1 -5 + -3 = -2 + -1x Combine like terms: -5 + -3 = -8 -8 = -2 + -1x Solving -8 = -2 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -8 + x = -2 + -1x + x Combine like terms: -1x + x = 0 -8 + x = -2 + 0 -8 + x = -2 Add '8' to each side of the equation. -8 + 8 + x = -2 + 8 Combine like terms: -8 + 8 = 0 0 + x = -2 + 8 x = -2 + 8 Combine like terms: -2 + 8 = 6 x = 6 Simplifying x = 6
| x^4-4x^3-12x^2+24x+5=0 | | 6(2n-1)+6=-3n | | C=35n+500 | | 6=1/36 | | C=2(3.16)r | | 5x-(x-2)=2x+6 | | 72+28+x=180 | | 3v^2+10=7v^2-15 | | x^4-6x^2+8x-5=0 | | 3a-1=95 | | L+w=36 | | f(x)=(x^2+25)(x^3+2x^2-15x) | | -2.3m=-12 | | 2/5=35/n | | 10-z=23 | | -(15/4)-(7) | | 1+y=3x | | 2.75+1.25+5.5= | | -3(5-9v)=257v | | f(x)=-10x^2+40 | | 3(0)-3y=2(0)+6 | | 3X/152 | | Y^2-90=13 | | 0.75(-12x-8)=x+34 | | 4(3x)^2/(2x)^2 | | 3(-1)-3y=2(0)+6 | | 5.1=c/7 | | √7/25x^2 | | -(15/4)-(7/1) | | 3(x+2)+2=5x+2(x-2) | | 4(3x)2/(2x)2 | | 2z^2+13z+21=0 |